Airport regulation in Europe: Is there need for a European Observatory? - Marques, R. C.; Brochado, A. (Transport Policy, 2008)
This paper provides an overview of how the major airports are regulated in Europe. In order to eliminate the potential of airports to exercise market power and protect the public interest, it has become increasingly necessary to set a common regulatory framework. We intend to discuss the need for a single regulator in Europe to monitor or establish the quality of service and the charges practiced by the airports, to ensure cost-relatedness, transparency and non-discrimination. The existing regulatory approaches regarding aeronautical charges and their economic implications are also analyzed. We propose the creation of a European Observatory for this sector.